Evasion differential game with many pursuers versus one evader whose control set is a sector - Ibragimov, Gafurjan; Alias, Idham Arif; Syed Mafdzot, Sharifah Anisah (Science Society of Thailand, 2017)
We study a simple motion evasion differential game of many pursuers x 1 , . . . , x m and one evader y in the plane. Maximum speeds of pursuers are equal to 1, and the control set of the evader is a sector S of radius greater than 1. We say that evasion is possible if x i (t) 6= y(t) for all t ¾ 0 and i = 1, . . . , m. We obtain conditions that guarantee the evasion from any initial positions of the pursuers and evader.